Post-activation potentiation enhancement induction strategies with different rest intervals on jump performance: a meta-analysis - Zhou, Y.; Zhang, X.; Wang, J. (Frontiers in Physiology, 2025)
Objective: This meta-analysis aimed to systematically evaluate the effects of post-activation potentiation enhancement (PAPE) on jump performance and explore its optimal induction strategies.